(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Amazon Inc., founded by Jeff Bezos in 1994, has grown from a small garage-based operation selling books into one of the world’s largest companies, with a market cap exceeding 1 trillion. Today, Amazon boasts a robust global supply chain management (SCM) system, integrating advanced technologies such as robotics, artificial intelligence, and cloud computing to ensure efficient, timely deliveries. Despite its cutting-edge logistics network, the company faces significant challenges, including reliance on third-party carriers like USPS and UPS for last-mile deliveries, the "bullwhip effect" distorting demand forecasting, and high shipping costs impacting profitability. This paper examines three potential solutions to address these challenges: increasing the use of Amazon Flex drivers for last-mile deliveries, integrating supply chain systems with suppliers, and automating warehouses with more robotic technology. Each solution is analyzed for its advantages, including improved delivery control, greater efficiency, and cost savings, as well as its drawbacks, such as increased operational complexity, high upfront investment costs, and potential labor issues. Drawing from personal experience as a trucking company assistant involved in Amazon’s SCM, the paper provides a detailed discussion on the practicality of these solutions, emphasizing the importance of balancing efficiency and cost while maintaining customer satisfaction and protecting Amazon’s reputation.